IMPACT WORKING CAPITAL TERHADAP PENINGKATAN PROFITABILITAS PADA KSU CAHAYA PERMATA - Risa Ratna Gumilang (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
This study aims to determine the effect of working capital on the level of profitability at KSU Cahaya Permata (Business Multipurpose Cooperative), namely by taking secondary data and using linear data analysis to determine the extent of a creation that is simpler than the Bank in the management system or the procedure for financial management, in increasing profitability for the benefit of the company itself, the uniqueness of this research is based on the researcher to conduct research research at KSU Cahaya Permata. The results of this study are that working capital has a significant effect on profitability, because the increasing working capital increases the level of profitability.